(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Assessment is a very important method of measurement of medical education. Anatomy is an essential part of undergraduate medical curriculum. Short answer question (SAQ) has a better content coverage as compared to long essay question. Objective: To be assess the pattern of SAQ in MBBS first professional written anatomy question papers of public universities of Bangladesh. Method: The cross-sectional study was conducted at Armed Forces Medical College in the department of Anatomy, Dhaka Cantonment. For this study, SAQ papers of anatomy of nine first professional MBBS examinations of Bangladesh University of Professionals (BUP), Dhaka University (DU) and Chittagong University (CU) from May 2017 to November 2021were collected. These were classified as parts and segments. Each segment was categorized as definition, draw and label, unique and open type. They werecalculated as number of segments as well as total weightage. Result: On analysis it was found that the percentage of weightage of definition type questions of BUP, DU and CU were 3.53±2.03, 2.43±1.42 and 2.89±1.12; draw and label type 12.84±4.44, 15.98±3.13,17.053±.65; unique type 24.16±9.88,31.33±6.14, 26.47±3.84 and for open type 56.13±4.77,60.72±5.15, 53.73+5.29. Significant difference was found in draw and label type question in between BUP and CU, in unique type question in between BUP and DU and DU and CU, in open type question in between DU and CU. Conclusion: Different types of SAQ are used to determine the level of cognitive domain. Proper distribution of types of SAQ shall ensure the proportion of these domain mentioned in the curriculum. JAFMC Bangladesh. Vol 19, No 2(December) 2023: 7-11